Characterization of Novel Cross-Reactive Influenza B Virus Hemagglutinin Head Specific Antibodies That Lack Hemagglutination Inhibition Activity - Kirkpatrick, Ericka (J Virol, 2020)
Humoral immune responses to influenza virus vaccines in elderly individuals are poorly adapted toward new antigenically drifted influenza virus strains. Instead, older individuals respond in an original antigenic sin fashion and produce much more cross-reactive but less potent antibodies. Here, we investigated four influenza B virus hemagglutinin (HA) head specific, hemagglutination inhibition-inactive monoclonal antibodies (MAbs) from elderly individuals. We found that they were broadly reactive within the B/Victoria/2/1987-like lineage, and two were highly cross-reactive with B/Yamagata/16/1988-like lineage viruses. The MAbs were found to be neutralizing, to utilize Fc effector functions, and to be protective against lethal viral challenge in a mouse model. In order to identify residues on the influenza B virus hemagglutinin interacting with the MAbs, we generated escape mutant viruses. Interestingly, escape from these MAbs led to numerous HA mutations within the head domain, including in the defined antigenic sites. We observed that each individual escape mutant virus was able to avoid neutralization by its respective MAb along with other MAbs in the panel, although in many cases binding activity was maintained. Point mutant viruses indicated that K90 is critical for the neutralization of two MAbs, while escape from the other two MAbs required a combination of mutations in the hemagglutinin. Three of four escape mutant viruses had increased lethality in the DBA2/J mouse model. Our work indicates that these cross-reactive antibodies have the potential to cause antigenic drift in the viral population by driving mutations that increase virus fitness. However, binding activity and cross-neutralization were maintained by a majority of antibodies in the panel, suggesting that this drift may not lead to escape from antibody-mediated protection. IMPORTANCE Understanding the immune response that older individuals mount to influenza virus vaccination and infection is critical in order to design better vaccines for this age group. Here, we show that older individuals make broadly neutralizing antibodies that have no hemagglutination-inhibiting activity and are less potent than strain-specific antibodies. These antibodies could drive viral escape from neutralization but did not result in escape from binding. Given their different mechanisms of action, they might retain protective activity even against escape variants.